2017
DOI: 10.3748/wjg.v23.i2.297
|View full text |Cite
|
Sign up to set email alerts
|

3-Dimensional liver volume assessment in patients with hepatitis B virus-related liver cirrhosis during long-term oral nucleos(t)ide analogues therapy

Abstract: AIMTo assess the effect of long-term oral nucleos(t)ide analogues (NUCs) therapy on liver volume change in patients with suppress hepatitis B virus (HBV)-related liver cirrhosis.METHODSWe reviewed the data of naïve patients with HBV-related liver cirrhosis, who had taken oral NUCs therapy, between 2003 and 2007 at Chonbuk University Hospital. We analyzed two consecutive sets of abdominal computerized tomography scans-one at the time of treatment initiation and another at the second-year follow-up. Liver volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Accumulating evidence has suggested that there is a significant volume reduction in cirrhotic livers as compared with normal livers [37, 38]. In addition, long-term oral nucleos(t)ide analogue therapy in patients with HBV-related liver compensated and decompensated cirrhosis leads to a significant increase in liver volume [39]. In this study, we found that although the liver volume was increased at all the time points after splenectomy, only the difference at 6 months postoperation reaches statistical significance, which may be attributed to the small sample size of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has suggested that there is a significant volume reduction in cirrhotic livers as compared with normal livers [37, 38]. In addition, long-term oral nucleos(t)ide analogue therapy in patients with HBV-related liver compensated and decompensated cirrhosis leads to a significant increase in liver volume [39]. In this study, we found that although the liver volume was increased at all the time points after splenectomy, only the difference at 6 months postoperation reaches statistical significance, which may be attributed to the small sample size of this study.…”
Section: Discussionmentioning
confidence: 99%